RF filter design using RF inductor and capacitor components - Abd. Rahman, Rozita (2010)
The project focuses on the design of planar radio frequency, RF, bandpass filter for a communication system. It is based on combining planar RF inductor and capacitor components. In the thesis, the chosen RF components are the spiral inductor and interdigital capacitor. Both components are first designed and simulated for optimum performances. The quality factor and component values were optimised. Optimum configurations were selected for the design of RF filters. The optimum value of filter order is first obtained as 3, using standard mathematical expression available in the literature. Two configurations of RF filters operating at 2 GHz and 10 GHz are then designed and simulated. It was found that the third order filter performs quite close to the desired specification, however, at the expense of high insertion loss within the passband. Nevertheless, it was observed that as the filter order increases, the bandpass filter has better performance. The passband slopes increases, indicating higher order response.